Da S. Daniele a Wrocław: il viaggio di sola andata di Wrocław, Biblioteka Uniwersytecka, Rehdigerianus 67 (Luc., Tim., part. or.)-From S. Daniele to Wrocław: A One-Way Journey to Wrocław, Biblioteka Uniwersytecka, Rehdigerianus 67 (Luc., Tim., part. or.) - Veronica Revello, VR (Ciceroniana On Line, 2020)
The article offers a codicological and palaeographic analysis of Wrocław, Biblioteka Uniwersytecka, Rehdigerianus 67, containing Lucullus, Timaeus and Partitiones oratoriae of Cicero. This contribution aims to demonstrate that the manuscript was written by the professional copyist Battista da Cingoli at San Daniele del Friuli in the atelier of Guarnerio d’Artegna, to whose hand some marginalia are here credited, in a year between 1458 and 1461. It should also be noted that part. or. represent an independent codicological unit, linked to the other two works at a different time from the copy. Finally, there is a brief philological overview, intended as a starting point for future studies of the author of these three Ciceronian texts.